THE CORRELATION BETWEEN SCIENCE PROCESS SKILLS AND BIOLOGY COGNITIVE LEARNING OUTCOME OF SENIOR HIGH SCHOOL STUDENTS - Ilma, Silfia; Al-Muhdhar, Mimien Henie Irawati; Rohman, Fatchur; Saptasari, Murni (University of Muhammadiyah Malang, 2020)
Science Process Skills (SPS) are the essential abilities which need to be mastered in learning biology to strengthen students? learning outcomes. The aim of this study was to analyze the relationship between SPS and biology Cognitive Learning Outcome (CLO) of senior high school students. The sample was 100 tenth graders in Malang. The correlational study used two test types as the instrument (i.e. essay and multiple choice). The essay instrument consisted of 10 items which were developed from SPS aspects (basic and integrated skills). Meanwhile, the biology CLO was measured using multiple choice test which consisted of 30 items. The collected data were analyzed using simple linear regression analysis. The results showed that the highest students? SPS aspect was observing (78.84%), while the lowest was predicting aspect (27.30%). In addition, the highest achievement of students? biology CLO was C1 (94.23%), while the lowest was C6 (33.46%). The regression analysis showed that there was a significant correlation between students? SPS and biology CLO, where the equation was Y = 27.988 + 0.311X. Therefore, it is crucial to consider SPS to be integrated into a learning activity by using various learning models that empowering these skills to improve students? biology CLO.